A PORTABLE LABORATORY WITH INTEGRATED LOCAL WISDOM FOR PHYSICS EDUCATION BASED ON LECTURER AND STUDENT PERCEPTIONS - Susanto, Rudi; Husen, Mohd Nizam; Lajis, Adidah (Malaysian Journal of Computer Science, 2021)
Learning a laboratory-based subject, such as physics, requires the student to be present in a laboratory for an optimum learning outcomes attainment. However, building laboratories with equipment are expensive where some institutions in certain countries could not afford it. This study aims to obtain data and perform analysis of the needs to develop portable physics laboratory based on information technology with embedded systems and the integration of local wisdom values in the contents. Samples involved in answering the questionnaire are from students and physics lecturers across the universities in Indonesia. The results of this research discuss perception from lecturers and students in 3 aspects about laboratory and learning physics, physics laboratory based on information technology and portable laboratory with integrated local wisdom (PL-ILW). Finding shows that 93.6% of the lecturers and 84.8% of the students are strongly agree and mostly agree for the development and implementation of a PL-ILW. The result shows that PL-ILW is suitable not only without the existence of a conventional laboratory, but it also suitable as add-ons where the portability is an advantage to be used at different locations.